2002
DOI: 10.1103/physrevd.66.025010
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on the topological open membrane

Abstract: Just as non-commutative gauge theories arise from quantising open strings in a large magnetic field, non-Abelian two-form gauge theories may conceivably be constructed by quantising open membranes in a large three-form magnetic background. We make some observations that arise in following this strategy, with an emphasis on the relation to the quantisation of volume-preserving diffeomorphisms (vpd). In particular, we construct consistent non-Abelian interactions of a two-form in 3+1 dimensions, based on gauge i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 45 publications
(58 reference statements)
1
36
0
Order By: Relevance
“…It has a long history of the struggle to achieve this goal, for example, see [10,11,14,[17][18][19]21,28,29]. One of the difficulty of the problem is that there seems to be no natural principle and therefore we have a variety of proposals with both merits and demerits.…”
Section: A2 Nambu Bracketmentioning
confidence: 98%
“…It has a long history of the struggle to achieve this goal, for example, see [10,11,14,[17][18][19]21,28,29]. One of the difficulty of the problem is that there seems to be no natural principle and therefore we have a variety of proposals with both merits and demerits.…”
Section: A2 Nambu Bracketmentioning
confidence: 98%
“…There are in the literature several persuasive but inconclusive arguments that Nambu brackets are a natural language for describing extended objects, for example: [2,6,7,14,18,27,31,34,36,40,46].…”
Section: Introductionmentioning
confidence: 99%
“…This model is a toy model for string theory in a background 3-form field, and was studied in [3,4,5,6], but rather from the point of view of the somewhat ill-defined boundary string theory. In [3] it was shown that in a particular decoupling limit a stack of M5-branes in a 3-form field the open membrane action of the M2-brane reduces to this particularly simple topological membrane model.…”
Section: Introductionmentioning
confidence: 99%